2012
DOI: 10.1038/ni.2242
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms that control the expression and activity of Bcl-6 in TH1 cells to regulate flexibility with a TFH-like gene profile

Abstract: SUMMARYT-bet and Bcl-6 are required to establish TH1 or TFH gene expression profiles, respectively. Here, we demonstrated that high interleukin 2 (IL-2) concentrations inhibited Bcl-6 expression in polarized TH1 cells. Mechanistically, the low amounts of Bcl-6 normally found in effector TH1 cells could not repress its target genes because a T-bet-Bcl-6 complex masked the Bcl-6 DNA-binding domain. TH1 cells increased their Bcl-6/T-bet ratio in response to limiting IL-2 conditions, allowing excess Bcl-6 to repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
408
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(441 citation statements)
references
References 45 publications
21
408
1
Order By: Relevance
“…Elegant experiments have used MHC class II tetramers to home in on antigen-specific T cells following influenza infection in mice and have shown that IL-2 administration selectively decreases the number of Tfh cells (CXCR5 1 PD1 1 ), but not other effector T cells (CXCR5 -PD1 -) [130]. Conversely, it has been shown that under conditions of IL-2 deprivation, Th1 cells can acquire a Tfh phenotype [131]. Thus, the availability of IL-2 in the local environment has significant consequences for the development and homeostasis of the Tfh population.…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elegant experiments have used MHC class II tetramers to home in on antigen-specific T cells following influenza infection in mice and have shown that IL-2 administration selectively decreases the number of Tfh cells (CXCR5 1 PD1 1 ), but not other effector T cells (CXCR5 -PD1 -) [130]. Conversely, it has been shown that under conditions of IL-2 deprivation, Th1 cells can acquire a Tfh phenotype [131]. Thus, the availability of IL-2 in the local environment has significant consequences for the development and homeostasis of the Tfh population.…”
Section: Il-2 Signalling Impairs Tfh Differentiationmentioning
confidence: 99%
“…Recent data suggest that early T cell differentiation is likely to be even more diverse than was appreciated previously [152], with a broad selection of functional phenotypes being generated, the most useful of which are then expanded selectively. Moreover, intermediate differentiation states exist, including a Tfh-like transitional stage shared by Tfh and Th1 cells [153], and phenotypical conversions are possible, such as the switch from Th1 to Tfh under conditions of limiting IL-2 [131]. These developments argue for a more nuanced view of T cell differentiation in type 1 diabetes that does not focus solely on Th1 cells, but also encompasses the possible involvement of IL-21-producing T cells such as Tfh, as well as T cells co-producing IFN-g and IL-17.…”
Section: Concluding Commentsmentioning
confidence: 99%
“…In B cells, Blimp1 induces plasma cell differentiation and blocks the GC B-cell differentiation program by repressing Bcl6 (8). This reciprocal antagonism also exists in T cells, as Blimp1 directly inhibits Bcl6 expression and supports differentiation of non-Tfh effector cells (2,(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Each of these domains can associate with specific corepressor complexes in B cells and macrophages. The Bcl6 DNA binding zinc fingers are required for Bcl6 activity in CD4 T cells in cell culture (4,12). The Bcl6 BTB domain participates in Tfh cell differentiation (13), most likely by interacting with BCOR (14) and perhaps other corepressors.…”
mentioning
confidence: 99%
“…In contrast to other types of polarization, differentiation into T FH cells is independent of Th1, Th2, Th17, and regulatory T cell differentiation programs, as T FH cells with features of other polarized T cells have been recognized (28,29). In particular, considerable flexibility between Th1 and T FH cells has been reported; namely, Th1 cells have been demonstrated to increase their B cell lymphoma 6 (Bcl-6)/T-bet ratio under limiting IL-2 conditions to become T FH -like cells (30). In this study, we dem- adopt some of the early T FH differentiation program in the peritoneal milieu.…”
Section: Discussionmentioning
confidence: 99%